The Association of Family Eating Behaviors With Children's Cognitive Functioning: A Cross-Sectional Study Among 3–6-Year-Old Mexican Children. (7th June 2021) - Aguayo, Liliana; Alam, Rifat B; Schwingel, Andiara; Cunningham, Solveig; Piñeros-Leaño, Maria
Abstract: Objectives: Little is known about the association of family eating behaviors with young children's cognitive development, particularly among non-White populations. The objective of this study is to determine if healthier family eating behaviors are associated with young Mexican children's cognitive functioning. Methods: We used cross-sectional data from a convenience sample of low-income child-mother dyads recruited from a public preschool in San Luis Potosi, S.L.P., Mexico. Using the Family Nutrition and Physical Activity (FNPA) questionnaire, mothers were asked to report the frequency of ten family eating behaviors (e.g., frequency of breakfast intake, family mealtimes, etc.). Children completed two cognitive tests: a working memory test of their ability to recall four words after a timed distraction (i.e., delayed recall); and a verbal fluency test, examined with a 60-second trial of word retrieval in response to "things people eat". The associations of family eating behaviors with children's working memory and verbal fluency were examined using multiple linear regression models adjusting for child sex, age, mother's age, education, and subjective socioeconomic status. Results: Study included 85 child-mother dyads; children's ages ranged from 3 to 6 years (4.58 ± 0.58) and mothers from 19 to 55 years (30.92 ± 8.49). Children had a mean working memory score of 2.24 ± 0.99 words recalled and retrieved a mean of 20.06 ± 5.26 words in the verbal fluency tests. Higher frequency of breakfast intake was associated with higher working memory scores (β = 0.56, P = 0.013). No other family eating practices were significantly associated with children's working memory. Children's verbal fluency scores were not significantly associated with family eating practices. Conclusions: Frequent breakfast intake was associated with young children's memory maintenance. Future research is needed to examine the mechanisms through which breakfast intake could benefit children's neurodevelopmental health. Funding Sources: This study was supported by the training grant "Illinois Transdisciplinary Obesity Prevention Program (I-TOPP)" funded by the National Institute of Food and Agriculture, United States Department of Agriculture (USDA) and support from the NIDDK.